Design, synthesis, molecular modelling and antitumor evaluation of S-glucosylated rhodanines through topo II inhibition and DNA intercalation - Ahmed I. Khodair; Fatimah M. Alzahrani; Mohamed K. Awad; Siham A. Al-Issa; Ghaferah H. Al-Hazmi; Mohamed S. Nafie (Taylor & Francis Group, 2023)
In the present study, 5-arylidene rhodanine derivatives 3a-f, N-glucosylation rhodanine 6, S-glucosylation rhodanine 7, N-glucoside rhodanine 8 and S-glucosylation 5-arylidene rhodanines 13a-c were synthesised and screened for cytotoxicity against a panel of cancer cells with investigating the effective molecular target and mechanistic cell death. The anomers were separated by flash column chromatography and their configurations were assigned by NMR spectroscopy. The stable structures of the compounds under study were modelled on a molecular level, and DFT calculations were carried out at the B3LYP/6-31 + G (d,p) level to examine their electronic and geometric features. A good correlation between the quantum chemical descriptors and experimental observations was found. Interestingly, compound 6 induced potent cytotoxicity against MCF-7, HepG2 and A549 cells, with IC50 values of 11.7, 0.21, and 1.7 µM, compared to Dox 7.67, 8.28, and 6.62 µM, respectively. For the molecular target, compound 6 exhibited topoisomerase II inhibition and DNA intercalation with IC50 values of 6.9 and 19.6 µM, respectively compared to Dox (IC50 = 9.65 and 31.27 µM). Additionally, compound 6 treatmnet significantly activated apoptotic cell death in HepG2 cells by 80.7-fold, it induced total apoptosis by 34.73% (23.07% for early apoptosis, 11.66% for late apoptosis) compared to the untreated control group (0.43%) arresting the cell population at the S-phase by 49.6% compared to control 39.15%. Finally, compound 6 upregulated the apoptosis-related genes, while it inhibted the Bcl-2 expression. Hence, glucosylated rhodanines may serve as a promising drug candidates against cancer with promising topoisomerase II and DNA intercalation.